2010
DOI: 10.1002/jsfa.4024
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of peptide fractions derived from cottonseed protein hydrolysate

Abstract: The results showed that the hydrolysate derived from cottonseed protein, particularly fraction III, could be a natural antioxidant source suitable for use as a food additive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 21 publications
1
38
1
Order By: Relevance
“…At 1 mg/mL, fraction I showed the strongest ·OH scavenging activity (28.5%) among four fractions, and its activity was significantly stronger than BSFH (12.7%). In the present study, the ·OH scavenging activity of BSFH was weaker than that of cottonseed protein hydrolysate (47.33% at 10 mg/mL) (Gao, Cao, & Li, 2010). Kim, Je, and Kim (2006) reported four fractions from hoki frame protein hydrolysate exhibited extremely strong ·OH scavenging activity (69.18% or more) at 0.5 mg/mL.…”
Section: ·Oh Scavenging Activitycontrasting
confidence: 50%
See 1 more Smart Citation
“…At 1 mg/mL, fraction I showed the strongest ·OH scavenging activity (28.5%) among four fractions, and its activity was significantly stronger than BSFH (12.7%). In the present study, the ·OH scavenging activity of BSFH was weaker than that of cottonseed protein hydrolysate (47.33% at 10 mg/mL) (Gao, Cao, & Li, 2010). Kim, Je, and Kim (2006) reported four fractions from hoki frame protein hydrolysate exhibited extremely strong ·OH scavenging activity (69.18% or more) at 0.5 mg/mL.…”
Section: ·Oh Scavenging Activitycontrasting
confidence: 50%
“…Fraction II showed the most powerful DPPH• scavenging activity (36.7%), followed by Fraction I (25.7%), and these two fractions exhibited significantly stronger activity than BSFH at 1 mg/ mL (P b 0.05). In recent years, Gao et al (2010) and Li, Han, and Chen (2008) also reported the DPPH•-scavenging peptides derived from food protein hydrolysates. In our research, as comparison, ascorbate displayed strong activity in scavenging DPPH• (94.4% at 0.1 mg/mL), while carnosine showed weak (7.4% at 10 mg/mL).…”
Section: Dpph• Scavenging Activitymentioning
confidence: 99%
“…The enhancement of antioxidative capacity in FCSM may be attributed to many active peptides derived from the CSM protein hydrolysates that can scavenge the free radicals. Gao, Cao, and Li (2010) demonstrated that cottonseed protein hydrolyzed with Neutrase contains peptides with strong antioxidant activity. In addition, previous study indicated that the cottonseed peptides prepared by the fermentation process displayed a dose-dependent effect on the free radical-scavenging activity, hydroxyl radical activity, metal-chelating ability, and reducing power (Sun et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…For every 100 kg of lint fiber ginned from cotton, 150 kg of cottonseed is produced (Yu et al, 2012). Thus, cottonseed is an abundant resource for oil, meal and protein for human consumption, animal feed, and industrial raw material (Coppock et al, 1987;Gao et al, 2010;He et al, 2013a;2014a;2014b;Kandasamy et al, 2008;Zhang et al, 2009). The chemical composition is an important parameter in evaluating cottonseed quality for these different applications.…”
Section: Introductionmentioning
confidence: 99%